On the nature and licensing conditions of n-phrases in Portuguese - PERES João Andrade (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada, 2000)
The present paper focuses on the syntactic and semantic nature of the expressions identified in the literature as n-words (preferably, n-phrases), and on their licensing conditions. Concerning their status, arguments will be given in favor of Ladusaw's 1992 thesis that these are existential (and non-specific, it is claimed) indefinites. In a brief excursus, it will be shown that other constructs engage in the process known as "negative concord". In the final part, an attempt will be made to offer a systematic picture of the intra-- and cross-sentential licensing conditions of classical n-phrases. In this regard, the paramount importance of contextual decreasing monotonicity becomes apparent.